A novel de novo GABRA2 gene missense variant causing developmental epileptic encephalopathy in a Chinese patient - Li Yang; Xingyu Wan; Ran Hua; Junhong Jiang; Baotian Wang; Rui Tao; De Wu (Annals of Clinical and Translational Neurology)
Abstract Background Variants in the GABRA2 gene, which encodes the α2 subunit of the γ‐aminobutyric acid A receptor, have been linked to a rare form of developmental and epileptic encephalopathy (DEE) referred to as DEE78. Only eight patients have been reported globally. This study presents the clinical presentation and genetic analysis of a Chinese family with a child diagnosed with DEE78, due to a novel GABRA2 variant. Methods Genetic diagnosis was performed using trio‐whole exome sequencing, followed by bioinformatics predictions of pathogenicity. Structural modeling assessed the potential impact of the variant. A mutant plasmid was constructed and transfected into 293 T cells. Western blotting (WB) was used to evaluate mutant protein expression, while co‐immunoprecipitation (Co‐IP) analyzed interactions with GABRB3 and GABRG2 proteins. Immunofluorescence (IF) assessed the subcellular localization of the mutant protein. Results The 6‐year‐old male proband presented with seizures starting at age two, along with global developmental delay and hypotonia. Genetic testing revealed a heterozygous de novo variant in GABRA2 gene (NM_000807: c.923C>T, p.Ala308Val). Structural modeling suggested that this variant is located within the extracellular domain, which may disrupt hydrogen bonding interactions with GABRB3 and GABRG2. WB and Co‐IP showed reduced protein expression and impaired interactions, potentially destabilizing the pentamer receptor complex. If analysis revealed that the variant did not affect subcellular localization. Conclusion This study identified a novel likely pathogenic GABRA2 extracellular domain variant in a Chinese family causing the DEE phenotype. The results expand the genotypic and phenotypic spectrum of GABRA2‐related DEE.